1989
DOI: 10.1111/j.1471-6402.1989.tb00984.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Male-Female Ratio at Work: Policewomen and Male Nurses

Abstract: Difficulties faced by women in work organizations are often explained as indirect consequences of their numerical minority. Their sex plays no role in these explanations: Men in a minority position are claimed to experience similar problems. The results of this empirical study challenge this: Policewomen are seen to face many of the disadvantages pointed out by Kanter (1977) and others, whereas male nurses enjoy advantages from being one of the few among female colleagues. Also, while the male majority in poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
1
12

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(136 citation statements)
references
References 8 publications
5
118
1
12
Order By: Relevance
“…Research shows that men working in contexts numerically dominated by women can avoid the negative consequences of gender imbalance and, in fact, often benefit from being in token positions (Heikes, 1991;Ott;Williams, 1992;Yoder & Sinnett, 1985). For example, Heikes (1991) found that men working in female-skewed contexts report positive experiences and increased performance motivation, and Ott (1989) and Yoder and Sinnett (1985) found that men report quicker advancement to management in female-skewed contexts.…”
Section: Gender Ratio Of the Workgroupmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that men working in contexts numerically dominated by women can avoid the negative consequences of gender imbalance and, in fact, often benefit from being in token positions (Heikes, 1991;Ott;Williams, 1992;Yoder & Sinnett, 1985). For example, Heikes (1991) found that men working in female-skewed contexts report positive experiences and increased performance motivation, and Ott (1989) and Yoder and Sinnett (1985) found that men report quicker advancement to management in female-skewed contexts.…”
Section: Gender Ratio Of the Workgroupmentioning
confidence: 99%
“…For example, Heikes (1991) found that men working in female-skewed contexts report positive experiences and increased performance motivation, and Ott (1989) and Yoder and Sinnett (1985) found that men report quicker advancement to management in female-skewed contexts.…”
Section: Gender Ratio Of the Workgroupmentioning
confidence: 99%
“…Also, a study of the military suggested some male advantage in selection for key assignments, which consisted of opportunities to command and serve as executive officer and senior enlisted advisor (U.S. General Accounting Office, 1998). The quicker promotion of men into leadership positions is prevalent or even accentuated in female-dominated fields (e.g., Maume, 1999;Ott, 1989;C. L. Williams, 1992C.…”
Section: Studies Of Actual Wages and Promotionmentioning
confidence: 99%
“…Thus, female managers commonly are members of a numerically small minority, whereas their male counterparts are members of a majority group. As Kanter and others argued, token status increases one's visibility (Taylor, Fiske, Etcoff, & Ruderman, 1978) and can have a number of negative implications for how one is perceived and treated, especially when the token is a woman (Crocker& McGraw, 1984;Ott, 1989;Yoder & Sinnett, 1985). In 2 Whereas the belief that effective female managers are especially concerned about relationships may reflect stereotypic beliefs about women in general, the belief that effective female managers are especially concerned about task accomplishment may reflect a more complex theory about women having to perform extremely well to succeed as managers.…”
Section: Theoretical Analysis Of Sex Differences In Leadership Stylementioning
confidence: 99%